The Analysis of Code Switching Found in The Twitter Account @natanattda - Putu Delita Tiswani Sanjaya; Ni Luh Nyoman Seri Malini; I Made Suastra (Jurnal Langua, 2023)
The phenomenon of code-switching occurs in everyday life as speech or text on social media. One example is found in Twitter, a social media platform that has received a lot of attention in recent years. This study aimed to determine (1) what types of code-switching are used and (2) why code-switching is used on Twitter accounts @natanattda. The research was carried out using qualitative methods. Reading and searching for tweets from the @natanattda account is a method of collecting data in this study. The theory applied when conducting this study was proposed by Poplack in Romaine (1995) about analyze the different types of code-switching. Another theory was proposed by Hoffman (1991) about the reasons for using code-switching. In this study, two points were discovered through data analysis. The first point was about the various types of code-switching, including Tag switching, Inter-sentential switching, and Intra-sentential switching. The second point was about the reasons for using code-switching. The most dominant type of code-switching found in the data is Inter-sentential switching. From the seven reasons for using the code-switching theory proposed by Hoffman (1991), only two reasons found from this account's tweets include talking about a particular topic and being emphatic about something (expressing solidarity). The most dominant reason for using code-switching found in the data is talking about a particular topic.